2006
DOI: 10.1016/j.jvs.2006.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Age-related variations of varicose veins anatomy

Abstract: The frequent occurrence of normal SVs in varicose limbs of all patients does not support the crucial role commonly credited to SVs in the pathogenesis of primary varicosities. Moreover, the SV trunks were normal in most varicose limbs from young patients. These findings suggest that varicose disease may progressively extend in an antegrade fashion, spreading from the STVs to the SVs. This hypothesis suggests that the saphenous trunks could be spared in the treatment of a relevant number of varicose legs. Prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 22 publications
4
43
1
3
Order By: Relevance
“…However, Caggiati demonstrated, that the saphenous vein was not altered in almost half of the varicose veins cases, which could confirm the theory of not only retrograde but also antegrade development of varicose veins [18]. Dodd revealed that in 61% of the limbs in young patients varicosities were limited to the tributaries of the saphenous vein and veins not connected directly with the saphenous vein, whereas in older patients VVs occurred in both saphenous vein and its tributaries [19].…”
Section: Venous Hypertensionmentioning
confidence: 79%
“…However, Caggiati demonstrated, that the saphenous vein was not altered in almost half of the varicose veins cases, which could confirm the theory of not only retrograde but also antegrade development of varicose veins [18]. Dodd revealed that in 61% of the limbs in young patients varicosities were limited to the tributaries of the saphenous vein and veins not connected directly with the saphenous vein, whereas in older patients VVs occurred in both saphenous vein and its tributaries [19].…”
Section: Venous Hypertensionmentioning
confidence: 79%
“…[5][6][7][8][9][10][11] Certain publications also suggested the hypothesis of a so-called ascending or multifocal development of varicose disease starting from the distal superficial venous network. 6,7,[9][10][11]17,18 Thus, the minimally invasive surgical approach focusing on the treatment of the varicose reservoir by phlebectomy, as described by Muller,19 is enjoying renewed attention, including with the conservation of a refluxing SV. 20 We describe here our midterm clinical and hemodynamic experience with this more limited surgical approach.…”
mentioning
confidence: 99%
“…Eine venöse Hypertension in den großen Venen mit primärer Klappeninsuffizienz und nachfolgender Dilatation der distalen Venenabschnitte ist nur in einem Teil der Fälle bereits zu Beginn nachzuweisen [1]. Nicht selten findet man -vor allem auch bei jüngeren Patienten -eine antegrade Entwicklung von Varizen mit pathologischen Refluxen und Ausweitungen von Venenwänden nur in Seitenästen, die Stammvenen sind (noch) nicht mitbetroffen [2][3][4].…”
Section: äTiologie Der Chronisch Venösen Insuffizienzunclassified